Veiled agency? Children, innovation and the archaeological record. (9th February 2021) - Sterelny, Kim
Abstract: Abstract: Children and subadults were obviously part of ancient human communities, and almost certainly, in important ways their activities were distinctive; they did not routinely act like scaled down adults. Yet their presence was quite cryptic, but not entirely hidden. Their lives and acts did leave traces, although these tend to be be fragile, ambiguous and fast-fading. In addition to pursuing the methodological issues posed by the detection of subadult lives, this special issue raises important questions about the role of children, and their willingness to experiment and play, on innovation. It is true that ethnographically known forager children are almost certainly more autonomous, experimental and adventurous than WEIRD children, and this was probably true of the young foragers of the early Holocene and late Pleistocene too. Their greater willingness to experiment probably fuelled a supply of variation, and perhaps occasionally adaptation as well, especially finding new uses for existing materials. Much more certainly, innovations tend to be noted, taken up and spread by adolescents. They were vectors of change, even if perhaps only rarely initiators of change.